Isolation, Purification and Structural elucidation of bioactive constituents from root bark of Crataeva magna Lour (DC) - RADHA krishnan meera (Journal of Global Pharma Technology, 2018)
Objective: The study was to isolate and characterize the bioactive phytoconstituents from Crataeva magna Lour (DC).Materials and methods: For isolation of the compounds, ethanolic extract of Crataeva magna Lour (DC) isolated first with petroleum ether, increasing amounts of EtOAc in petroleum ether and finally with methanol yielded a number of fractions. The proportion of solvent systems used to obtain CM-01 and CM-02 were hexane-EtOAc (80: 20) and EtOAc –methanol (98:2) from fractions 5 and 8.Results: The subsequent structures of isolated compounds were elucidated by various spectrophotometric analysis. Mass spectrum of CM-01 and CM-02 showed a parent molecular ion (M+) peak at 382 gm/mol and 614 gm/mol respectively. In the 1H- NMR spectrum of CM-01 has 0.728 (methyl H), 2.439 (OH ), 2.764 (long chain CH2), 3.953(H in CH2 adjacent to OH ) where as in the 1H- NMR spectrum of CM-02, 3.9-4.2 (CH3 protons), 5.7 (OH group), 6.2-7.2 (Aromatic protons)Conclusion: From the physical, chemical and spectral characteristic CM-01 and CM-02 were concluded as phytosterols (Ceryl alcohol (Hexacosan -1-ol)) and macropolyphenol (Tannic acid).Keywords: Crataeva magna Lour (DC), phytosterols, macropolyphenol.